2014
DOI: 10.1289/ehp.1206157
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure and Cardiac Electrical Conduction in Excised Rat Hearts

Abstract: Background: Bisphenol A (BPA) is used to produce polycarbonate plastics and epoxy resins that are widely used in everyday products, such as food and beverage containers, toys, and medical devices. Human biomonitoring studies have suggested that a large proportion of the population may be exposed to BPA. Recent epidemiological studies have reported correlations between increased urinary BPA concentrations and cardiovascular disease, yet the direct effects of BPA on the heart are unknown.Objectives: The goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 60 publications
(89 reference statements)
4
45
0
2
Order By: Relevance
“…Stwierdzono także, że ekspozycja na bisfenol A zwięk-sza ryzyko nadciśnienia i choroby wieńcowej (3,16,20). Pomimo stosunkowo znacznej liczby badań na temat negatywnego wpływu BPA na układ sercowo--naczyniowy (1,2,12,15,34), dokładny mechanizm tego działania nie został do końca poznany. Można przypuszczać, iż ma on związek z neurotoksyczną aktywnością bisfenolu A. Należy jednak zaznaczyć, że mimo licznych badań dotyczących wpływu BPA na komórki i włókna nerwowe (25,29), efekty jego wpływu na unerwienie serca nie zostały do tej pory opisane.…”
Section: Praca Oryginalnaunclassified
See 1 more Smart Citation
“…Stwierdzono także, że ekspozycja na bisfenol A zwięk-sza ryzyko nadciśnienia i choroby wieńcowej (3,16,20). Pomimo stosunkowo znacznej liczby badań na temat negatywnego wpływu BPA na układ sercowo--naczyniowy (1,2,12,15,34), dokładny mechanizm tego działania nie został do końca poznany. Można przypuszczać, iż ma on związek z neurotoksyczną aktywnością bisfenolu A. Należy jednak zaznaczyć, że mimo licznych badań dotyczących wpływu BPA na komórki i włókna nerwowe (25,29), efekty jego wpływu na unerwienie serca nie zostały do tej pory opisane.…”
Section: Praca Oryginalnaunclassified
“…Udowodniono mianowicie, że bisfenol A po podaniu dożylnym odkłada się między innymi w sercu (44) i uszkadza znajdujące się tam mitochondria, co wpływa negatywnie na metabolizm mięśnia sercowego oraz obniża wydolność tego narządu (1,22). Inne badania wykazały, iż nawet niskie dawki bisfenolu A w diecie mogą powodować przerost mięśnia sercowego i wzrost jego wagi (24) oraz udowodniły BPA-zależne zwolnienie przewodzenia bodź-ców elektrycznych w sercu izolowanym (34). Ponadto stosunkowo dobrze poznane są stany chorobowe układu krążenia spowodowane bisfenolem A, do któ-rych należy zaliczyć: arytmię, podwyższone ciśnienie krwi, stany zapalne serca i naczyń oraz miażdżycę (2,12).…”
Section: Cgrp)unclassified
“…These estrogen-like effects of BPA increased arrhythmia frequencies in response to β-adrenergic stress in isolated hearts from female rats and mice, but not those of males (13). Additional in vitro studies have also demonstrated that acute exposures to high concentrations of BPA could decrease the rate and force of contractility and cardiac conduction velocity in hearts from female rats (14, 15) and to a lesser extent in the male heart (16). In vivo studies involving analysis of large numbers of male and female CD-1 or C57Bl/6n mice exposed throughout life to a wide range of BPA doses have also identified a number of sex and strain specific exposure-related effects (1719).…”
Section: Introductionmentioning
confidence: 98%
“…Our laboratory has also examined the effects of BPA on cardiac function using excised Langendorff-perfused hearts 122 . Although we did not observe arrhythmias in our studies, BPA exposure adversely affected cardiac electrical conduction in a concentration-dependent manner.…”
Section: Bisphenol-a (Bpa)mentioning
confidence: 99%